2007
DOI: 10.1103/physrevd.75.043506
|View full text |Cite
|
Sign up to set email alerts
|

Averaging in spherically symmetric cosmology

Abstract: The averaging problem in cosmology is of fundamental importance. When applied to study cosmological evolution, the theory of macroscopic gravity (MG) can be regarded as a long-distance modification of general relativity. In the MG approach to the averaging problem in cosmology, the Einstein field equations on cosmological scales are modified by appropriate gravitational correlation terms. We study the averaging problem within the class of spherically symmetric cosmological models. That is, we shall take the mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 70 publications
6
67
0
Order By: Relevance
“…The solutions to the macroscopic field equations (2), with an FLRW ansatz for the macroscopic metric, have recently been studied in [24,[34][35][36][37], where it was found that the extra terms involving the correlation tensor Z α µ β[γ νσ] take the same form in the macroscopic field equations that a spatial curvature curvature term takes in Einstein's equations. In fact, for a spatially flat macroscopic metric, and with spatial correlations only, it can be shown that extra terms in Eq.…”
Section: A Macroscopic Flrw Solutionsmentioning
confidence: 99%
“…The solutions to the macroscopic field equations (2), with an FLRW ansatz for the macroscopic metric, have recently been studied in [24,[34][35][36][37], where it was found that the extra terms involving the correlation tensor Z α µ β[γ νσ] take the same form in the macroscopic field equations that a spatial curvature curvature term takes in Einstein's equations. In fact, for a spatially flat macroscopic metric, and with spatial correlations only, it can be shown that extra terms in Eq.…”
Section: A Macroscopic Flrw Solutionsmentioning
confidence: 99%
“…Various combinations of the parameters t B0 , r c and r E were checked, but even though one of them reproduces roughly the same value as the H D (z D ) analysis, the physical significance of this term remains doubtful. curvature term is also known from Macroscopic Gravity [8][9][10]. At first order in E one has R D ∝ a −2 D for the averaged curvature which is similar to the FLRW case.…”
Section: Simple Models For E(r) and T B (R)mentioning
confidence: 83%
“…A very general manner to deal with the averaging problem relies on the exact covariant Macroscopic Gravity formalism by Zalaletdinov [7]. Macroscopic gravity has been applied to spherically symmetric cosmology by Coley et al in [8][9][10], observational aspects of the resulting dynamics were discussed in [11]. A result of this averaging is the appearance of an additional spatial curvature term in the dynamical equations.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is significant for cosmology because the governing equations for the model evolution differ from the Friedmann equations by the additional backreaction term which depends on the scale factor in the same manner as the spatial curvature [8,11]. This means that the dynamical curvature parameter is decoupled from the geometrical value of the curvature, distorting the luminosity distance-redshift relation.…”
Section: Introductionmentioning
confidence: 99%